Good Corporate Governance, Company Life Cycle, and CSR Disclosure on Firm Value: The Mediating Role of Earning Management - Hana Bilqis; Noviany Rahmatika, Dien; Indriasih, Dewi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of good corporate governance, company life cycle, and corporate social responsibility (CSR) disclosure on firm value, with earnings management as a mediating variable. The study used a quantitative approach on 34 consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period (170 observations). Data were analyzed using panel data regression and the Sobel test. The results show that the independent board of commissioners, company life cycle, and CSR disclosure influence earnings management, while only the independent board of commissioners has a direct effect on firm value. Earnings management mediates the influence of the independent board of commissioners and company life cycle on firm value.